Proliferacja broni masowego rażenia - Balawender, Dominik (OTO Agencja Reklamowa, 2014)
Development and proliferation of Weapons of Mass Destruction still is one of the major global issues, that to needs be solved by the international community. Ending of the Cold War did not cease state and non-state actors actions focused on acquisition of the WMD. The ongoing attempts to develop or buy Weapons of Mass Destruction by terrorist organizations and states such as Iran and North Korea make this global issue even more important nowadays. International governmental organization are taking multiple activies to constrain the development and proliferation of the WMD. The aim of this article is to present the most important documents of international law that concerns the idea of constraing the proliferation of biological, chemical and nuclear weapons, created within these organizations and also to describe the contemporary activities of these organizations that leads to realization of aforementioned goal.
Keywords: broń masowego rażenia; terroryzm międzynarodowy